Genital warts treatment: Beyond imiquimod - Jianwei Yuan; Guoying Ni; Tianfang Wang; Kate Mounsey; Shelley Cavezza; Xuan Pan; Xiaosong Liu (Taylor & Francis Group, 2018)
Genital warts are one of the most common sexually transmitted diseases worldwide. The disease is a result of infection with low-risk types of human papillomaviruses, mostly type 6 and 11. Current therapies for genital warts are mainly ablative, or alternatively topical application of imiquimod cream and sinecatechin (polyphenon E) ointment to the warts. However, low patient compliance and high recurrence rate are significant problems for the treatment of genital warts by imiquimod and ablative therapies. We summarise recent literature in this area and propose combining imiquimod with other therapies to increase the efficacy of imiquimod.